What Am I Drinking? Vision Modulates the Perceived Flavor of Drinks, but No Evidence of Flavor Altering Color Perception in a Mixed Reality Paradigm - Stäger, Lorena; Roel Lesur, Marte; Lenggenhager, Bigna (Frontiers in Psychology, 2021)
It is well established that vision, and in particular color, may modulate our experience of flavor. Such cross-modal correspondences have been argued to be bilateral, in the sense that one modality can modulate the other and vice versa. However, the amount of literature assessing how vision modulates taste is remarkably larger than that directly assessing how taste might modulate vision. This is more exaggerated in the context of cross-modal contrasts (when the expectancy in one modality contrasts the experience through another modality). Here, using an embodied mixed reality setup in which participants saw a liquid while ingesting a contrasting one, we assessed both how vision might modulate basic dimensions of taste perception and how the flavor of the ingested liquid might alter the perceived color of the seen drink. We replicated findings showing the modulation of taste perception by vision but found no evidence of flavor modulating color perception. These results are discussed in regard to recent accounts of multisensory integration in the context of visuo-gustatory cues and bilateral cross-modulations. Our findings might be important as a first step in understanding bilateral visuo-gustatory cross-modulations (or the lack of them) and might inform developments using embodied mixed reality technologies.